An evaluation of sexual history evidence in sexual crimes cases in Malaysia - Mohamad Yunus, Mohamad Ismail (Sweet & Maxwell Malaysia, 2018)
This article is to evaluate the subject of the relevance of sexual history evidence in Malaysia. This includes the issue of the admissibility of evidence about the complainant’s sexual history, which is an issue of relevancy that is usually determined under the so-called rape shield law. As an illustration, if A is on trial for the rape of B, should evidence that B flirted with C and D earlier in the evening be allowed? If B previously had consensual sex with both C and D, does that show that she is more likely to have consented to sex with A? Would it make a difference if on each occasion had she been drinking, picked up by the men in the same circumstances, and had sex in the same way?”. This issue has been debated widely due to its prejudicial nature. Therefore, in this article, the comparison with regards to the position of sexual history evidence in several countries like England, India, Singapore as well as Malaysia will be made. In view of this debatable issue, the effect of allowing the sexual history evidence in sexual crime trial, as well as the end product of limiting such evidence in the court of law, shall be explained thoroughly. Lastly, an attempt is also made to come up with an evaluation as to whether the law should be reformed or is there any other suggestions and recommendations to improve the current position of sexual history evidence and if it were to happen in Malaysia.